The study of the characteristics of sand concrete based on marble waste sand - Bebhalilou, Mohamed Ichem; Belachia, Mouloud; Houari, Hacene; Abdelouahed, Assia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present study aims to valorize the waste and in particular the waste from the Fil-fila quarry. The main reason for choosing the waste from this quarry was the need to reduce the impact on the environment (by reducing stockpiling) and the raw material cost (economic reason).
Keywords: sand concrete; wastes; marble; substitution; durability; performance; beton piaskowy; odpady; marmur; substytut; trwałość